A systemic approach to the analysis of Slavic (Ukrainian and Polish) oikonymy from a diachronic perspective - Redkva, Yaroslav (Wydawnictwo JAK, 2017)
The article traces the formation of the oikonymic system, toponymic space and toponymic landscape, twenty-four place names of of Shchyrets povit in the Lviv Land Ruske Voivodeship over the 14th to the 15th centuries, using a systemic approach to analysis of historical Western Ukrainian oikonymy. The onset of certain derivational and semantic types of place names models are also established in the article, i.e.: *-any (Dobrzany/Dobriany, Łubiany/Liubiany), *-ovb (Krasów/Krasiv; Kahujów/ Kahuyiv; Tatarynów/Tataryniv), plural (patronymic, lineage, ethnic) names (Horbacze/Horbachi, Honiatycze/Honiatychi, Koniuszki/Koniushky, Sroki/Soroky, Czerkasy/Cherkasy, Nowosiółki/ Novosilky), physiographic names (Piaski/Pisky, Ostrów/Ostriv). These names are elements of a language system (to be more precise of two intertwined systems — Ukrainian and Polish), and they were created and adapted by their speakers in accordance with the laws of the system, and genetically connected with the community that populated the area.
Keywords: place names, onomastic space, historical Western Ukrainian oikonyms, comparative oikonymic studies, oikonymic systems